Pharmacokinetic and pharmacodynamic study of lenograstim for hematopoietic stem cell mobilization: a prospective randomized study for optimal apheresis. Issue 5 (29th March 2019) - Kang, Jihoon; Hong, Jung Yong; Yoon, Dok Hyun; Kim, Jeong Eun; Kim, Kyu‐pyo; Kim, Shin; Lee, Kyoung Min; Park, Jung Sun; Lee, Ji Sung; Suh, Cheolwon
Abstract : BACKGROUND: This study evaluated the correlation between the pharmacokinetics and pharmacodynamics of granulocyte colony‐stimulating factor (lenograstim) and the impact of initiation time of apheresis on stem cell mobilization in patients with multiple myeloma. STUDY DESIGN AND METHODS: Twenty‐four patients with multiple myeloma were randomized into one of the two groups (early vs. late). Lenograstim at 10 μg/kg/day once daily was injected for at least 4 consecutive days. Apheresis was initiated 2 hours after the fourth dose of lenograstim in the early collection group and 16 hours after the fourth dose of lenograstim in the late collection group. Blood sampling for pharmacokinetics was performed within 30 minutes before, and 1, 2, 6, and 24 hours after the fourth dose of lenograstim. RESULTS: Overall, the two groups (early vs. late, n = 10 vs. 14) exhibited similar baseline characteristics including age, sex, subtype of myeloma, stage distribution, and myeloma‐associated symptoms. No correlation was found between plasma lenograstim concentration and peripheral blood (PB) CD34+ cell counts or hematopoietic progenitor cells. In the late collection group, the median number of apheresis procedures for minimal collection was significantly lower (early vs. late: 2 vs. 1; p = 0.04) and there was a higher number of total collected PB CD34+ cells in a single session of apheresis (1.4 vs. 3.1; p = 0.06). There were no differences in median overall PB stem cell collection efficiency. CONCLUSION: Late collection positively impacted the number of apheresis procedures for minimal collection, with numerically improved PB stem cell collection efficiency at first apheresis in patients with multiple myeloma.